Radiation Defects in Heterostructures 3C-SiC/4H-SiC - A.A. Lebedev; G.A. Oganesyan; V.V. Kozlovski; I.A. Eliseyev; P.V. Bulat (Crystals, 2019)
The effect of 8 MeV proton irradiation on n-3C-SiC epitaxial layers grown by sublimation on semi-insulating 4H-SiC substrates has been studied. Changes in sample parameters were recorded using the Hall-effect method and judged from photoluminescence spectra. It was found that the carrier removal rate (Vd) in 3C-SiC is ~100 cm−1, which is close to Vd in 4H-SiC. Compared with 4H and 6H silicon carbide, no significant increase in the intensity of the so-called defect-related photoluminescence was observed. An assumption is made that radiation-induced compensation processes in 3C-SiC are affected by structural defects (twin boundaries), which are always present in epitaxial cubic silicon carbide layers grown on substrates of the hexagonal polytypes.